Herbicidal Activity and Molecular Docking Study of Novel ACCase Inhibitors - Ye, Fei; Ma, Peng; Zhang, Yuan-Yuan; Li, Ping; Yang, Fei; Fu, Ying (Frontiers in Plant Science, 2018)
Acetyl-CoA carboxylase (ACCase) is an important target enzyme for the development of new bleaching herbicides. On the basis of structure-activity relationships and active subunit combinations, a series of novel 2-phenyl-3-cyclohexanedione enol ester derivatives was designed and synthesized by coupling and acylation reactions. The preliminary biological tests indicated good post-emergent herbicidal activity at a dosage of 150-300 g ai/ha, superior to that of clethodim against barnyard grass. Compound 3d was safe with respect to maize, even at a dosage of 300 g ai/ha. Compound 3d showed the best ACCase inhibitory activity in vitro, with a value of 0.061 nmol h-1 mg-1 protein, superior to that of clethodim. Molecular docking modeling showed that compound 3d and clethodim had the same interactions with surrounding residues, leading to an excellent combination with the active pocket of ACCase. That may have been the mechanism responsible for the death of the barnyard grass. The present work suggests compound 3d as a potential lead structure for further development of novel ACCase inhibitors.